2013
DOI: 10.1177/1557988313509834
|View full text |Cite
|
Sign up to set email alerts
|

Sex, HIV, and the Internet

Abstract: With the increasing pervasiveness of social media, the Internet has become an important venue for dating and sex. Not only does the Internet introduce a unique array of opportunities and risks for men who have sex with men (MSM), it also presents a valuable means through which to study sexual behavior. In this study, data on what men report in their online profiles were collected from two dating/hookup websites to explore possible geographical differences in men's sexual preferences and expectations (N = 5,588… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…The online profiles of MSM were used to explore geographical variations in the sexual preferences and expectations of MSM across 15 selected cities in the US. The findings showed that the use of condoms and the status of reported HIV differed significantly in these cities [18].…”
Section: Introductionmentioning
confidence: 87%
“…The online profiles of MSM were used to explore geographical variations in the sexual preferences and expectations of MSM across 15 selected cities in the US. The findings showed that the use of condoms and the status of reported HIV differed significantly in these cities [18].…”
Section: Introductionmentioning
confidence: 87%
“…A useful source for examining intragroup stigma among MSM and between sexual partners is through Internet-based sex-seeking websites and apps. Online sex-seeking has become increasingly popular [ 19 , 20 ]; an estimated 40% of MSM in the United States have used the Internet to look for a sex partner [ 21 - 25 ]. Research suggests that MSM who have met their partners online report more sex partners [ 23 , 24 , 26 , 27 ], a higher prevalence of condomless anal intercourse [ 24 , 27 , 28 ], and a higher prevalence of sexually transmitted infections (STIs) [ 23 , 24 , 29 - 31 ].…”
Section: Introductionmentioning
confidence: 99%